2008
DOI: 10.1016/j.ucl.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic Sperm Injection (ICSI) – What are the Risks?

Abstract: In vitro fertilization (IVF) used in combination with intracytoplasmic sperm injection (IVF/ICSI) allows otherwise sterile couples to become parents. Despite the fact that the oldest IVF conceived baby 1 is now over 30 years of age, questions about the safety of assisted reproductive technologies persist. The long term follow-up of the first generation of IVF/ICSI offspring offers a clearer picture of the safety of these technologies; despite these recent studies, however, there is still only an incomplete pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 65 publications
2
55
0
Order By: Relevance
“…<A>Discussion At present, assisted reproductive techniques (such as ICSI and IVF) account for about 5% of births in the Western world (Lewis and Kumar, 2015) and, with ICSI, some checkpoints of natural fertilization are bypassed. As a result, low-quality spermatozoa with features such as abnormal morphology, low motility, damaged DNA, aneuploidy and poor zona binding potential that are not normally able to participate in natural fertilization, may be selected for ICSI procedure inadvertently (Cummins and Jequier, 1995;Tournaye, 2003;Alukal and Lamb, 2008). As spermatozoa have no mechanism to repair DNA damage, DNA strand breaks can be transferred to the oocyte during ICSI, and will rely on the oocyte to repair them (Lewis and Kumar, 2015).…”
Section: Changes In Sperm Hyaluronic-acid-binding and Hyperactive Motmentioning
confidence: 99%
“…<A>Discussion At present, assisted reproductive techniques (such as ICSI and IVF) account for about 5% of births in the Western world (Lewis and Kumar, 2015) and, with ICSI, some checkpoints of natural fertilization are bypassed. As a result, low-quality spermatozoa with features such as abnormal morphology, low motility, damaged DNA, aneuploidy and poor zona binding potential that are not normally able to participate in natural fertilization, may be selected for ICSI procedure inadvertently (Cummins and Jequier, 1995;Tournaye, 2003;Alukal and Lamb, 2008). As spermatozoa have no mechanism to repair DNA damage, DNA strand breaks can be transferred to the oocyte during ICSI, and will rely on the oocyte to repair them (Lewis and Kumar, 2015).…”
Section: Changes In Sperm Hyaluronic-acid-binding and Hyperactive Motmentioning
confidence: 99%
“…So far, however, follow-up studies of children born after ICSI compared with children born after conventional IVF have not been conclusive regarding the risks of congenital malformations, imprinting diseases and health problems. In vitro fertilization, in general, is associated with multiple gestations and increased risk of congenital abnormalities (including hypospadias) [29]. ICSI, in particular, carries an increased risk of endocrine abnormalities, as well as epigenetic imprinting effects [29].…”
Section: Sperm Dna Integrity Assaysmentioning
confidence: 99%
“…In vitro fertilization, in general, is associated with multiple gestations and increased risk of congenital abnormalities (including hypospadias) [29]. ICSI, in particular, carries an increased risk of endocrine abnormalities, as well as epigenetic imprinting effects [29]. Although the absolute risk of any of these conditions remains low, current data is limited and study populations are heterogenic [29][30][31][32].…”
Section: Sperm Dna Integrity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IVF is not harmless and has been reported to be associated with complications including higher incidence of multiple births and a low but discrete risk of other genetic disorders. Several studies have shown that IVF performed by ICSI carries a higher risk of a major birth defect (in particular, genitourinary defects and epigenetic syndromes such as Beckwith-Wiedemann syndrome and Silver-Russell dwarfism) compared with a naturally conceived infant [6,[8][9][10]. The American Society of Reproductive Medicine considers ICSI a safe and effective procedure but notes that it may carry some increased risk for the transmission of selected genetic abnormalities to offspring [11].…”
mentioning
confidence: 99%